The relationship between motor skills and psychosocial factors in young children: A test of the elaborated environmental stress hypothesis. (8th September 2017) - Mancini, Vincent O.; Rigoli, Daniela; Roberts, Lynne D.; Heritage, Brody; Piek, Jan P.
Abstract : Background: The elaborated environmental stress hypothesis (EESH) provides a framework that describes how motor skills may indirectly cause internalizing problems through various mediating psychosocial factors. While there is evidence to support this framework, little is known about how the proposed relationships may vary across different stages of development. Aims: This study aimed to investigate whether peer problems and perceived self‐competence mediated the relationship between motor skills and internalizing problems in pre‐primary children, and at 18‐month follow up. Sample: A community sample of 197 pre‐primary school children ( M = 5.40 years, SD = 0.30 years; 102 males, 95 females) participated at Time 1, with 107 completing the Time 2 follow‐up. Methods: Standardized instruments were used to measure motor skills and verbal IQ. Perceived self‐competence was measured using a self‐report measure. Participant peer problems and internalizing problems were measured using teacher report. Age, gender, and verbal IQ were included as covariates. Results: Mediation analysis using PROCESS showed that the relationship between motor skills and internalizing problems was mediated by peer problems at Time 1. At Time 2, the relationship was mediated by peer problems and perceived physical competence. Conclusions: The current results indicate the EESH may function differently across different periods of development. The transition from pre‐primary to Grade 1 represents a time of important cognitive and psychosocial development, which has implications for how the relationship between motor skills and internalizing problems can be understood. These findings highlight potential age‐appropriate targets for psychomotor interventions aiming to improve the emotional well‐being of young children.